Resonance of graphene nanoribbons doped with nitrogen and boron: a molecular dynamics study - Wei, Ye; Zhan, Haifei; Xia, Kang; Zhang, Wendong; Sang, Shengbo; Gu, Yuantong (Beilstein Journal of Nanotechnology, 2014)
Based on its enticing properties, graphene has been envisioned with applications in the area of electronics, photonics, sensors, bio-applications and others. To facilitate various applications, doping has been frequently used to manipulate the properties of graphene. Despite a number of studies conducted on doped graphene regarding its electrical and chemical properties, the impact of doping on the mechanical properties of graphene has been rarely discussed. A systematic study of the vibrational properties of graphene doped with nitrogen and boron is performed by means of a molecular dynamics simulation. The influence from different density or species of dopants has been assessed. It is found that the impacts on the quality factor, Q, resulting from different densities of dopants vary greatly, while the influence on the resonance frequency is insignificant. The reduction of the resonance frequency caused by doping with boron only is larger than the reduction caused by doping with both boron and nitrogen. This study gives a fundamental understanding of the resonance of graphene with different dopants, which may benefit their application as resonators.
Keywords: dopant; graphene; molecular dynamics simulation; natural frequency; quality factor; resonance